Study of Biomass in Two Mangrove Ecosystems - Sandra Sukmaning Aji; Rony Marsyal Kunda; Frenly Marvi Selano; Ucu Rahayu; Maman Rumanta (Postgraduate, University of Mataram, 2023)
This study aims to determine the storage of biomass in the mangrove ecosystem of Jakarta Bay compared to Ambon Bay. This research used descriptive quantitative method. Sampling technique using the Point Center Quarter Method (PCQM) which was measured around the chest height of mangrove trees (DBH). Data analysis was performed using an allometric equation where each mangrove plant has a specific gravity. The results of this study indicated that the composition of mangrove species in Ambon Bay consists of 6 mangrove species, namely: Bruguiera cylindrica (L.) Bl, Rhizophora apiculata Bl, Sonneratia alba Smith, Aegiceras corniculatum (L.) Blanco, Avicennia officinalis L, Ceriops tagal. In the ecosystem, Rhizophora apiculata Bl and Sonneratia alba Smith had higher biomass values compared to the other four species. Meanwhile, in Jakarta Bay, the composition of mangrove plants is dominated by Sonneratia alba Smith. The subsurface biomass in the Jakarta Bay and Ambon region is lower than the aboveground biomass.